Inappropriate eating behavior: a longitudinal study with female adolescents - Leonardo de Sousa Fortes; Sebastiao de Sousa Almeida; Flavia Marcele Cipriani; Maria Elisa C. Ferreira (Sociedade de Pediatria de São Paulo, 2014)
Objective: To evaluate the inappropriate eating behaviors (IEB) of female adolescents over a one-year period. Methods: 290 adolescents aged between 11 and 14 years old participated in the three research stages (T1: first four months, T2: second four months and T3: third four months). The Eating Attitudes Test (EAT-26) was applied to assess the IEB. Weight and height were measured to calculate body mass index (BMI) in the three study periods. Analysis of variance for repeated measures was used to analyze the data, adjusted for the scores of the Body Shape Questionnaire and the Brazil Economic Classification Criteria. Results: Girls at T1 showed a higher frequency of IEB compared to T2 (p=0.001) and T3 (p=0.001). The findings also indicated higher values for BMI in T3 in relation to T1 (p=0.04). The other comparisons did not show statistically significant differences. Conclusions: IEB scores of female adolescents declined over one year.